Endoplasmic Reticulum Adaptation and Autophagic Competence Shape Response to Fluid Shear Stress in T24 Bladder Cancer Cells - Del Favero, Giorgia; Zeugswetter, Michael; Kiss, Endre; Marko, Doris (Frontiers in Pharmacology, 2021)
Accumulation of xenobiotics and waste metabolites in the urinary bladder is constantly accompanied by shear stress originating from the movement of the luminal fluids. Hence, both chemical and physical cues constantly modulate cellular response in health and disease. In line, bladder cells have to maintain elevated mechanosensory competence together with chemical stress response adaptation potential. However, much of the molecular mechanisms sustaining this plasticity is currently unknown. Taking this as a starting point, we investigated the response of T24 urinary bladder cancer cells to shear stress comparing morphology to functional performance. T24 responded to shear stress protocol (flow speed of 0.03mL/min, 3h) by increasing significantly their surface area. When exposed to deoxynivalenol-3-sulfate (DON-3-Sulf), bladder cells increased this response in a concentration dependent manner (0.1-1µM). DON-3-Sulf is a urinary metabolite of a very common food-contaminant mycotoxin (deoxynivalenol, DON) and was already described to enhance proliferation of cancer cells. Incubation with DON-3-Sulf also caused the enlargement of the endoplasmic reticulum (ER), decreased the lysosomal movement and increased formation of actin stress fibers. Similar remodeling of the ER and area spread after shear stress were observed upon incubation with the autophagy activator rapamycin (1-100nM). Performance of experiments in presence of chloroquine (CQ, 30μM) further contributed to shed light on the mechanistic link between adaptation to biomechanical stimulation and ER stress response. At the molecular level, we observed that ER reshaping was linked to actin organization with the two components mutually regulating each other. Indeed, we identified in the ER stress-cytoskeletal rearrangement an important axis defining the physical/chemical response potential of bladder cells and created a workflow for the further investigation of urinary metabolites, food constituents and contaminants, as well as for pharmacological profiling.